PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER BERBANTUAN WORKSHEET PADA MATERI SEGIEMPAT DAN SEGITIGA UNTUK SISWA KELAS VII SMP/MTs - Merry Merry; Maimunah Maimunah; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Computer based media for learning mathematics on quadrilateralsand triangles topics is using worksheet. Worksheet is using by student for write solution,so that student work can be seen by teacher. The topics of quadrilaterals and triangleshas potency to be developed vissually by using a computer device to fasilitate studentsto understand this topics. The research model used is a research and developmentmodel adapted according to Borg and Gall. The aim of this research is to develop validand practical computer based media for learning mathematics using worksheet onquadrilaterals and triangles for seventh grade. The subjects were 23 students at 7thgrade Junior High School Metta Maitreya Pekanbaru. The instruments used were amaterial validation sheet, media validation sheet, and student response questionnaire.The analyzed data and disccusion showed that computer based media for learningmathematics using worksheet is valid with an average score of 3,50 by materialvalidator and 3,99 by media validator. This media is also qualified and practical withan average of student responses was 3,52.KeyWords: Computer based media, worksheet, quadrilaterals and tringales